Christie's Trade Mark Application: Appointed Person (Trade Marks) Daniel Alexander Q.C.: 17 January 2020 BL O-040-20; [2020] R.P.C. 8. Issue 4 (20th October 2021) - Unknown
: H1 Trade marks – Opposition proceedings – ZOHARA – Likelihood of confusion – Identifying the average consumer – Assessing aural similarity – Differences in pronunciation – Global assessment – Appeal to Appointed Person